In Silico Pharmacological Analysis of a Potent Anti-Hepatoma Compound of Mushroom Origin and Emerging Role as an Adjuvant Drug Lead - Fernando, Muthuthanthriege Dilusha Maduranganie; Adhikari, Achyut; Senathilake, Nambukara Helambage Kanishka Sithira; de Silva, Egodage Dilip; Nanayakkara, C.M.; Wijesundera, Ravindra Lakshman Chundananda; Soysa, Preethi; de Silva, Babaranda Gammacharige Don Nissanka Kolitha (My University, 2019)
Mushrooms are well-known to possess a continuum of anticancer metabolites that are vital in the development of anticancer adjuvant drug leads based on natural products. Owing to the fact that conventional cancer therapeutic me- thods were failed to lessen mortality caused by cancer to the estimated level with occurrence of adverse side effects, anticancer agents isolated from natural mushroom sources unarguably make an experimental research area worth mass focus today. The current study was targeted on in vitro cytotoxicity and in silico predictive pharmacological analysis of a flavonoid compound isolated from Fulvifomes fastuosus mushroom. Targeted compound was isolated from the mushroom using different chromatographic methods and identified by NMR spectrometry and mass spectrometry. Cytotoxicity experiments were carried out using MTT assay and apoptotic cells were identified by ethidium bro- mide/acridine orange staining. The SwissADME tool, BOILED-Egg construc- tion model and Swiss target protein prediction software have been used to per- form in silico predictive pharmacological analysis. The isolated compound has been identified as 2-(3,4-dihydroxyphenyl)-6-[(E)-2-(3,4-dihydroxyphenyl)eth- enyl]-5'-methylspiro[2H-furo[3,2-c]pyran-3,2'-furan]-3',4-dione by spectro- metric methods. The result of MTT assay showed that 2-(3,4-dihydroxy- phenyl)-6-[(E)-2-(3,4-dihydroxyphenyl)ethenyl]-5'-methylspiro[2H-furo[3,2- c]pyran-3,2'-furan]-3',4-dione has potent anticancer activity for hepatoma against Hep-G2 cell line (IC50 = 20.8 μg/ml) being less toxic to normal CC-1 epithelial cells (IC50 = 167.00 μM). The cells treated with compound exhibited apoptotic features such as cellular shrinkage, nuclear fragmentation and con- densed cytoplasm. In summary, 2-(3,4-dihydroxyphenyl)-6-[(E)-2-(3,4-di- hydroxyphenyl)ethenyl]-5'-methylspiro[2H-furo[3,2-c]pyran-3,2'-furan]-3',- 4-dione has shown potent anticancer properties against hepatoma with less cytotoxicity effect on normal cells. Furthermore, in silico study has revealed that properties of 2-(3,4-dihydroxyphenyl)-6-[(E)-2-(3,4-dihydroxyphenyl)eth- enyl]-5'-methylspiro[2H-furo[3,2-c]pyran-3,2'-furan]-3',4-dione may contri- bute to making a high absorption and clearance of the test compound as not interfering with the therapeutic failure of the compound. The properties of 2-(3,4-dihydroxyphenyl)-6-[(E)-2-(3,4-dihydroxyphenyl)ethenyl]-5'-methylspiro [2H-furo-[3,2-c]pyran-3,2'-furan]-3',4-dione were compatible with well-known anticancer drug lapatinib. In conclusion, 2-(3,4-dihydroxyphenyl)-6-[(E)-2- (3,4-dihydroxyphenyl)ethenyl]-5'-methylspiro[2H-furo[3,2-c]pyran-3,2'-furan] -3',4-dione has a high tendency to act as a good anticancer adjuvant drug in the treatment of hepatoma.
Keywords: Anti-Hepatoma Compound, Fulvifomes fastuosus, In Silico Pharmacological Analysis, Drug Lead